2014
DOI: 10.1007/s11693-014-9158-2
|View full text |Cite
|
Sign up to set email alerts
|

On Brucella pathogenesis: looking for the unified challenge in systems and synthetic biology

Abstract: Brucellosis is a zoonotic infection transmitted to humans from infected animals and is one of the widely spread zoonoses. Recently, six species were recognized within the genus Brucella wherein B. melitensis, B. suis and B. abortus are considered virulent for humans. While these species differ phenotypically by their pattern of metabolic activities, there has been an imperative need to understand pathogenesis of Brucella species. It has been foreseen that creating a human vaccine for Brucellosis would entail d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Out of 12 species, B. melitensis , B . abortus , and B. suis are considered to be the most important human pathogens with varying pathogenicity [ 2 , 3 ]. B. melitensis and B. suis except biovar 2, are the most virulent species, whereas B. abortus provokes milder illness [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Out of 12 species, B. melitensis , B . abortus , and B. suis are considered to be the most important human pathogens with varying pathogenicity [ 2 , 3 ]. B. melitensis and B. suis except biovar 2, are the most virulent species, whereas B. abortus provokes milder illness [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis is uncontrolled in wildlife, and the fear that it might be used in bioterrorism still exists [2]. Out of 12 phenotypically recognized species, B. melitensis, B. suis, B. abortus, and B. canis are well-known human pathogens [3,4]. Brucella melitensis is considered the most virulent species causing severe disease in humans.…”
Section: Introductionmentioning
confidence: 99%
“…These findings can be correlated with a recent study also reporting the detection of possible CRISPRS in Brucella genomes (Chiliveru et al, 2015). Moreover, a diguanylate cyclase (a CRISPR-related protein) was also detected in some Brucella genomes and this augments the fact that a CRISPR system might actually exist (Chiliveru et al, 2015). This finding was consistent with our results as well, with all sequenced isolates having a diguanylate cyclase.…”
Section: Detection Of Crisprssupporting
confidence: 93%
“…One possible CRISPR structure was detected in each of the sequenced genomes of length 82bp and having one spacer, and this result indicated that Brucella might have acquired resistance against phages and therefore have become more pathogenic in the process. These findings can be correlated with a recent study also reporting the detection of possible CRISPRS in Brucella genomes (Chiliveru et al, 2015). Moreover, a diguanylate cyclase (a CRISPR-related protein) was also detected in some Brucella genomes and this augments the fact that a CRISPR system might actually exist (Chiliveru et al, 2015).…”
Section: Detection Of Crisprssupporting
confidence: 87%